Guidelines for oral, pharyngeal and laryngopharyngeal surgery during COVID-19 pandemic - Husain, Parvez; Husain, Benazeer; Ahmed, Shaheen Khalil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
The pandemic due to the new respiratory infection known as coronavirus 2019 disease (COVID-19), caused by the SARS-CoV-2 virus, has triggered an unprecedented disruption in the normal activity of ENT, oral, and pharyngeal surgery departments worldwide, delaying routine patient care and elective surgical interventions. ENT, oral, and pharyngeal surgeons are one of the healthcare groups with the highest risk of nosocomial infection because of the close contact that occurs with asymptomatic and symptomatic patients with SARS-CoV-2 infection through the oral cavity and laryngopharynx. The purpose of this document has been to update the available evidence for the safe and effective management and treatment in elective and emergency surgeries, and hospitalization, while minimizing as much as possible the risk of infection for the ENT, oral, and laryngopharyngeal surgeon, health workers and patients. This document aims to clarify the most significant aspects and develop a common protocol for the surgical management of patients with COVID-19 in ENT, oral, and maxillofacial surgery during the acute stage of spread and subsequent control of the pandemic in our country.